Technical note: Low‐cost MR‐compatible pneumatic respiratory organ motion simulator for the development of MR‐guided thermal therapy. Issue 7 (7th June 2022) - Kim, Kisoo; Jones, Peter; Diederich, Chris; Ozhinsky, Eugene
Abstract: Background: In magnetic resonance (MR)‐guided thermal therapy, respiratory motion can cause a significant temperature error in MR thermometry and reduce the efficiency of the treatment. A respiratory motion simulator is necessary for the development of new MR imaging (MRI) and motion compensation techniques. Purpose: The purpose of this study is to develop a low‐cost and simple MR‐compatible respiratory motion simulator to support proof‐of‐concept studies of MR monitoring approaches with respiratory‐induced abdominal organ motion. Methods: The phantom motion system integrates pneumatic control via an actuator subsystem located outside the MRI and coupled via plastic tubing to a compressible bag for distention and retraction within the MRI safe motion subsystem and phantom positioned within the MRI scanner. Performance of the respiratory motion simulator was evaluated with a real‐time gradient echo MRI pulse sequence. Results: The motion simulator can produce respiratory rates in the range of 8–16 breaths/min. Our experiments showed the consistent periodic motion of the phantom during MRI acquisition in the range of 3.7–9 mm with 16 breaths/min. The operation of the simulator did not cause interference with MRI acquisition. Conclusions: In this study, we have demonstrated the ability of the motion simulator to generate controlled respiratory motion of a phantom. The low‐cost MR‐compatible respiratory motion simulator can be easily constructed from off‐the‐shelf and 3D‐printed parts based on open‐source 3D models and instructions. This could lower the barriers to the development of new MRI techniques with motion compensation.